Exploring students’ statistical problem-solving processes using GeoGebra Classroom: a junior high school case study - Widy Lestari; Rini Setianingsih; Yurizka Melia Sari (Journal Focus Action of Research Mathematic (Factor M), 2025)
Problem solving is the core goal in learning mathematics. However, TIMSS and PISA results show that Indonesian students' problem-solving abilities are still low. This study aims to describe the process of junior high school students in solving statistics problems using Polya's stages, supported by GeoGebra Classroom as an interactive visual learning tool. This descriptive qualitative research involved 31 grade VIII junior high school students as participants, who then selected three subjects through purposive sampling. Data were collected through tests, interviews, and field notes, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that highly category problem-solving subjects fulfilled Polya's stages. Medium category subjects completed most of Polya's stages, although some information was missing in the answer. Meanwhile, low category subjects could not solve the problem and did not fulfill Polya's stages. This study concluded that students who follow Polya's stages tend to perform better. Unlike prior research, this study shows how integrating GeoGebra Classroom can support student engagement in each stage of Polya's model. These findings emphasize integrating technology-based non-routine tasks to improve students' problem-solving ability.